2021
DOI: 10.1021/acs.joc.1c00844
|View full text |Cite
|
Sign up to set email alerts
|

Formylation and Bromination of Pyrrolo[2,1-a]isoquinoline Derivatives with Bromoisobutyrate and Dimethyl Sulfoxide

Abstract: We have developed an efficient formylation of pyrroloisoquinolines using bromoisobutyrate and dimethyl sulfoxide as carbonyl reagent. Various formylated pyrroloisoquinolines could be prepared in good yields (up to 94%). This formylation process can be easily scaled up to gram scale with good yield. In most cases of pyrroloisoquinolines without methoxy groups, the combination of bromoisobutyrate and dimethyl sulfoxide could act as a bromination reagent, delivering brominated pyrroloisoquinolines in acceptable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…Ishikura [11b] and Sawant [11e] have also prepared symmetric and unsymmetric bisheterocycles with heterocycle‐derived thioethers under DMSO‐based reaction systems in their studies respectively. We also found that thioethers can serve as key intermediates for formylation and bromination in our previous studies [13,15] …”
Section: Resultsmentioning
confidence: 55%
See 4 more Smart Citations
“…Ishikura [11b] and Sawant [11e] have also prepared symmetric and unsymmetric bisheterocycles with heterocycle‐derived thioethers under DMSO‐based reaction systems in their studies respectively. We also found that thioethers can serve as key intermediates for formylation and bromination in our previous studies [13,15] …”
Section: Resultsmentioning
confidence: 55%
“…The results indicate that thioether 9 may act as a key intermediate in this process. The hypothesis can also be supported by the facts that this kind of thioethers have been easily transformed to other functionalized molecules according to reports from others [2,8,11] and us [13,15] . Previously, further transformations of methylthiomethylenation products prepared in DMSO‐based systems to olefin and aldehyde have been successfully demonstrated by the groups of Huang 8a and Cheng 2a respectively.…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations